Characterization of biochar from rice hulls and wood chips produced in a top-lit updraft biomass gasifier - James, M.; Yuan, W.; Boyette, M. D.; Wang, Donghai H.; Kumar, A. (My University, 2016)
The objective of this study was to characterize biochar produced from rice hulls and wood chips in a top-lit updraft gasifier. Biochar from four airflows (8, 12, 16, or 20 L min-1) and two insulation conditions (not insulated or insulated with 88.9 mm of fiberglass on the external wall of the gasifier) were evaluated. Measurement of elemental composition, higher heating value (HHV), and BET surface area and proximate analyses of the biochar were carried out. It was found that the airflow rate and reactor insulation significantly influenced the chemical composition of the biochar depending on the biomass type. For instance, the carbon content of biochar from rice hulls decreased from 40.9% to 27.2% and the HHV decreased from 14.8 to 10.2 MJ kg-1 as the airflow increased from 8 to 20 L min-1 when the reactor was insulated. In contrast, the carbon content of biochar from wood chips increased from 82% to 86% and the HHV stayed stable at 32.0 to 33.2 MJ kg-1 at the same conditions. Despite these variations, the BET surface area of biochar from both biomass types increased with increased airflow and additional insulation. For example, rice hull biochar had a maximum BET surface area of 183 m2g-1 at 20 L min-1 airflow with insulation. The BET surface of biochar from wood chips peaked at 405 m2 gg-1 at the same conditions.
Citation: James, M., Yuan, W., Boyette, M. D., Wang, D., & Kumar, A. (2016). Characterization of biochar from rice hulls and wood chips produced in a top-lit updraft biomass gasifier. Transactions of the Asabe, 59(3), 749-756. doi:10.13031/trans.59.11631
Keywords: Biochar; Biomass; Gasification; Top-Lit Updraft Gasification; Calorific Value; Insulation